Sulfonate based ionic liquid incorporated polymer electrolytes for Magnesium secondary battery. Issue 9 (13th June 2019) - Ponmani, S.; Ramesh Prabhu, M.
ABSTRACT: The polymer electrolytes comprising of PVdF-HFP/PVAc/Mg(ClO4 )2 as salt based polymer blend electrolytes derived from the addition of varying amounts of 1-ethyl – 3-methylimidazolium trifluoromethane sulfonate [EMITF], as dopant were synthesized in the form of films by solution-casting method. The XRD and FTIR patterns confirm the formation of an amorphous phase and also that complex formation between the polymers, salt and ionic liquid. The SEM images show that the polymer electrolyte exhibit a enormous pores, remarkably, the maximum ionic conductivity is obtained in the case of the typical polymer system I3 is found to be 9.122 × 10 −4  Scm −1 at 303 K.